A comparison of two forms of the continuity equation in the Trifecta bovine pericardial aortic valve. Issue 1 (March 2016) - Chambers, John B; Parkin, Denise; Roxburgh, James; Bapat, Vinayak; Young, Christopher
Abstract: Aim: To compare the classical and simplified form of the continuity equation in small Trifecta valves. Methods: This is a retrospective analysis of post-operative echocardiograms performed for clinical reasons after implantation of Trifecta bioprosthetic valves. Results: There were 60 patients aged 74 (range 38–89) years. For the valves of size 19, 21 and 23mm, the mean gradient was 11.3, 10.7 and 9.7mmHg, respectively. The effective orifice areas by the classical form of the continuity equation were 1.4, 1.7 and 1.9cm 2, respectively. There was a good correlation between the two forms of the continuity equation, but they were significantly different using a t -test ( P <0.00001). Results using the classical form were a mean 0.11 (s.d. 0.18)cm 2 larger than those using the simple formula. Conclusion: Haemodynamic function of the Trifecta valve in the small aortic root is good. There are significant differences between the classical and simplified forms of the continuity equation.